Assessment of Factors contributed to Urinary Tract Infection (UTI) incidence in Sulaimani Teaching Hospital - Lafi, Samir Y. (Sulaimani Journal for Pure and Applied Sciences, 2010)
The study objectives are to assess the incidence of the risk factors that contribute to the (UTI), and to find out the relationship between UTI and some demographic characteristic such as age, gender, marital status, and educational level. A descriptive study was carried out in the Sulaimani Teaching Hospital (Kurdistan Region), The data were collected through the use of constructed questionnaire, which consisted of two parts: the firs one consist of (6) items which include the demographic information, and the second part consist of (13) items include contributing factors to (UTI).The study started from the middle of August 2007 up to the end of June 2008.To achieve the objectives of the study, a non-probability (purposive) sample of (50) patient: males, and females, who had (UTI), and admitted to the teaching hospital from the period of august 2007 up to April of 2008.The content validity of the instrument was established through a penal of (9) experts. Reliability of the instrument was determined through the split-half approach, (r=78). Data was gathered by interview technique using the questionnaire formal and data was analyzed by application of descriptive and inferential statistical method. The results of the study indicate that there is no association between (age, sex, level of education and marital status) and occurrence of UTI.
Keywords: Contributed factors; Urinary tract; infection; E coli